Gelarnya Sarjana Pendidikan, tapi Enggan Menjadi Pendidik: Bukti Kegagalan Sistem atau Kemunafikan Individu? - Mahmud Masulin; Fanny Irna Rachman; Rosita Sari; Sifa Aulia Hidayat; Windana Jopan Marbun (Aljabar : Jurnal Ilmuan Pendidikan, Matematika dan Kebumian, 2026)
The phenomenon of education graduates who are reluctant to enter the teaching profession has become an increasingly alarming issue amid the regeneration crisis of educators in Indonesia. This study aims to explore the factors causing the low interest of education students in becoming teachers and to critically analyze whether this phenomenon constitutes evidence of educational system failure or a reflection of individual hypocrisy. The research employed a descriptive qualitative method through a systematic literature review of 25 journal articles published between 2020 and 2026, thematically analyzed using Braun and Clarke’s framework. The findings revealed two opposing narratives: the “system failure” narrative, highlighting structural factors such as low teacher welfare, complex administrative burdens, limited career paths, and the mismatch between educational curricula and workplace demands; and the “individual hypocrisy” narrative, emphasizing shifts in students’ professional identity during their studies, the gap between idealistic expectations and reality, and pragmatic career choices. The synthesis indicates that the phenomenon is not binary but represents a complex interaction between systemic and individual factors. The implications of this research suggest the need for a transformative approach in teacher recruitment systems, structural welfare improvements, and strengthening professional identity formation during pre-service education.